KARAKTERISASI PADI BERAS MERAH ASAL KABUPATEN SEKADAU PADA FASE GENERATIF DI TANAH PODZOLIK MERAH KUNING ( PMK ) - MAINANDO, MAINANDO; WASI'AN, WASI'AN; ASTINA, ASTINA (Jurnal Sains Mahasiswa Pertanian, 2018)
THE GENERATIVE PHASE CHARACTERIZATION OF RED RICE FROM SEKADAU REGENCY IN RED-YELLOW PODZOLIC SOIL (RYP)Â Mainando (1), Wasi'an (2) and Astina (2)(1) Student at the Faculty of Agriculture and (2) Lecturers at the Faculty of Agriculture University of TanjungpuraÂ ABSTRACTThe morphological characteristics of Ensalang and Nanga Taman of red rice needed to be record. This is to provide an identity, in the assembly of varieties with desirable characters. This research aims to determine the morphological characters of the generative phase of Ensalang and Nanga Taman red rice which were grown Red Yellow Podzolik (RYP). The research was conducted in experimental garden of the Faculty of Agriculture of Tanjungpura University Pontianak for 66 days, from June 25th to August 29th 2017. The research used a complete Randomized Design Pattern (RDP), consisting of 2 treatment rice type i,e Ensalang and Nanga Taman. Each treatment was repeated 8 times, and each replication consisted of 5 plant samples. These observation variables were flowering time, grain tip color, panicle bud, panicle type, plant height, plant age, maximum number of tillers, number of productive tillers, panicle length, 100 g weight, number of per panicle grain, yield per polybag and environmental observation. The result of the characterization of red rice morphology of Ensalang and Nanga Taman in generative phase have different characteristic and characteristic on the color of grain tip, panicle outlet, and weight of 100 grains. Quantitative character differences are based on the T test results. The same morphological characteristics between the two types of red rice rice are panicle type, plant height, panicle length ,time of flowering of plant age, number of productive tillers, number of grain of proboscis and number of paddy unhulled rice.Keywords: Generative phase, morphological character, red rice, Ensalang and Nanga Taman.